A multiple view interactive environment to support MATLAB and GNU/Octave program comprehension - Lessa, I. (2022)
Program comprehension plays an important role in Software Engineering. In fact, many of the software lifecycle activities depend on program comprehension. Despite the importance of MATLAB and Octave programing languages in the Engineering and Statistical communities, little attention has been paid to the conception, implementation and characterization of tools and techniques for the comprehension of programs written in these languages. Considering this scenario, this paper presents a Multiple View Interactive Environment (MVIE) called OctMiner that supports the comprehension of programs developed in the aforementioned languages. OctMiner provides a set of coordinated visual metaphors that can be adjusted in accordance with the comprehension goals. An example is presented to illustrate the main functionalities of OctMiner in a real scenario of program comprehension.